MEDICINAL BIOMAGNETISM PROTOCOL IN THE TREATMENT OF DIABETES MELLITUS - Prates Macedo, Niceia; Bastos dos Santos Gonçalves, Rebeca; Souza Santos, Jefferson; Mara Rambo Martini, Angela; Viapiana Bossa, Adriane (Health and Society, 2023)
Currently, several treatments have been studied in order to restore health. A very promising treatment option is through the use of magnets. The exposure of cells to the Static Magnetic Field (SMF) is able to affect cell behavior by rebalancing its hydrogen potential (pH), which was previously dysfunctional, and may help control the signs and symptoms of diseases in patients with diabetes mellitus (DM) that may present subclinical states of infectious diseases. Medicinal Biomagnetism (BM) is a non-invasive integrative therapy that uses magnets as a tool with the aim of rebalancing the body’s natural pH, allowing the return to normal health conditions. With BM, it is possible to identify and correct dysfunctions that can lead to, or sustain, infectious pathologies, through the protocol proposed by Dr. David Goiz Martínez, helping to improve the signs and symptoms associated with diabetes mellitus, contributing to the general improvement of the individual. Objective: this work aims to present a BM protocol to aid in the treatment of DM. It also seeks a comprehensive view of other protocols not considered in Martínez’s proposal and suggests their incorporation. Materials and Methods: the article is a literature review in which 42 references were used, 05 of which were used to prepare the protocol. Results: protocol script with step-by-step DM treatment with BM. Conclusion: BM is a complementary and integrative technique with prophylactic potential in metabolic, endocrine and pathogenic disorders, easy to apply, inexpensive and with relatively quick results, with very low side effects. Future prospects: they are necessary to prove the proposed protocol.